Business Strategy Analysis of Contemporary Nature Tourism Development "The Le Hu Garden Indonesia" - Sitompul, Sari D; Hamdi , Edi; Anindita , Rina; Munandar , Agus (Innovative: Journal Of Social Science Research, 2025)
Le Hu Garden Indonesia is a natural tourism service provider that was founded in 2016 in Deli Serdang, North Sumatra. Its mission is to become the top option for top tourist services by completely satisfying all of its clients. Using SWOT and QSPM, the appropriate approach is required to realize this objective. This study looks at how development techniques can be applied to Le Hu Garden's commercial operations. The findings revealed that quadrant II, or grow and build, represented Le Hu Garden's strategic position as determined by the internal external matrix (IE). This demonstrates the requirement for a strategy in order for the business to expand and improve. Utilizing social media to spread information and promote products is a key approach with the highest attractiveness value of 2.58, according to the strategy chosen in QSPM. This explains why social media today has a significant influence on the marketing of the travel sector